2017
DOI: 10.1007/s00404-017-4559-6
|View full text |Cite
|
Sign up to set email alerts
|

Birth management and fetal outcome in multiple gestation: analysis of 1.444 births

Abstract: We conclude a vaginal delivery of twin appears safe if experienced staff monitor birth weight discrepancies, birth interval, and blood values consequently. A good outcome also for the second twin delivered spontaneously is nevertheless feasible if experienced staff is available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In a large-scale retrospective study, it was concluded that vaginal twin delivery appears safe if experienced staff monitor birth weight differences, birth interval, and blood values (15). In a comprehensive randomized study, no difference was observed between fetal and neonatal mortality rates and severe neonatal morbidity when comparing VB and CB in twin pregnancies between 32 and 38 weeks with the first twin in vertex presentation (4,14).…”
Section: Discussionmentioning
confidence: 99%
“…In a large-scale retrospective study, it was concluded that vaginal twin delivery appears safe if experienced staff monitor birth weight differences, birth interval, and blood values (15). In a comprehensive randomized study, no difference was observed between fetal and neonatal mortality rates and severe neonatal morbidity when comparing VB and CB in twin pregnancies between 32 and 38 weeks with the first twin in vertex presentation (4,14).…”
Section: Discussionmentioning
confidence: 99%
“…Chorionicity is responsible for adverse perinatal outcomes for twins [ 3 , 7 , 8 ]. About half of all twins are born before 37 weeks’ gestation or with a birth weight < 2500 g [ 9 ]. Monochorionic twins have higher rates of mortality and morbidity than dichorionic twins and peripartal mortality is approximately twice as high than for dichorionic twins [ 4 , 7 , 10 , 11 ].…”
Section: Background/introductionmentioning
confidence: 99%
“…There has therefore been much discussion in the past about the optimal mode of birth for multiple pregnancies. Some studies have shown a higher risk of adverse outcomes for both twins or the second twin after vaginal birth compared to planned CS, which led to a large increase in CS rates during the last years [ 9 , 12 – 16 ]. The findings of the Twin Birth Trial were ambivalent with regard to vaginal versus caesarean birth for twin pregnancies: the study showed neither a significant increase or decrease in the risk of foetal or neonatal death or morbidity for twin pregnancies between 32 + 0 and 38 + 6 weeks of gestation, with the lead twin in cephalic position [ 17 ].…”
Section: Background/introductionmentioning
confidence: 99%